Pengaruh Fasilitas Kerja, Lingkungan Kerja Dan Kompensasi Terhadap Kinerja Karyawan (Studi pada PT Pancamanah Utama Lamongan) - Jaffan, Jacky; Hidayati, Nur; Bastomi, Mohamad (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study attempts to ascertain the concurrent effects of remuneration, work environment, and work facilities on the productivity of PT Pancamanah Utama Lamongan personnel. The participants in this study were staff members of PT Pancamanah Utama Lamongan. This study employs quantitative methods. In order to collect data for this case study, non-probability sampling is used to distribute questionnaires to PT Pancamanah Utama Lamongan personnel. A saturated sample was used to calculate the sample size, and 85 responders were found. Multiple linear regression and determination tests were used to evaluate the data. Based on the data analysis results, the F test results demonstrate that PT Pancamanah Utama Lamongan employees' performance is significantly impacted by their work environment, remuneration, and amenities all at the same time. Additionally, the results of the t test indicate that PT Pancamanah Utama Lamongan employees' performance is influenced by their work environment, amenities, and pay. The determination test findings demonstrate that the dependent variable, employee performance, can be predicted by the percentage of 62%, which explains the independent factors, namely normative commitment, continuity commitment, and career development. Additionally, in this study, the data collecting technique may be carried out by monitoring visitors' desire to fill out and follow up with them so that, when presented with a questionnaire, they can promptly and accurately fill it out. Keywords: Employee Performance, Normative Commitment, Continuity Commitment, and Career Development.